USM COMMUNITY-INDUSTRY ENGAGEMENT PROGRAMMES TO FOCUS ON B40 GROUP - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 29 June 2015 – Universiti Sains Malaysia (USM) would further enliven the industry and community engagement programmes by giving more focus on the involvement of the B40 household group, those which are economically less capable and with an average household income being in the lowest 40 percent.